Navigating Business Opportunities and Challenges in 5G Communication Technology: Insights from Asean Case Studies - Wendy Junaidi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2026)
The presence of the fifth generation (5G) communication technology has become the digital transformation cornerstone across Southeast Asia, offering opportunities that have never emerged before, innovation, and connectivity across sectors. In the ASEAN region, 5G has the role of technological and strategic driver boosting the digital ecosystem, supporting Industry 4.0, and strengthening the competitiveness through integration with Artificial Intelligence (AI), Internet of Things (IoT), and cloud computing. However, apart from its transformative potential, 5G development has still not yet been distributed evenly due to policy fragmentation and spectrum allocation challenges, including the infrastructure readiness level. This research is meant to explore the business opportunities and challenges around 5G implementation through case studies from prominent markets in ASEAN, covering Singapore, Malaysia, Thailand, Vietnam, and Indonesia. By utilizing the knowledge from policy analysis, recent industry reports published in 2022-2025, and interviews with 10 consultants from IT implementers executing the 5G projects across the ASEAN region, this study identifies key factors supporting the 5G monetization success, evaluates the corporation adoption strategy, and confers imperative policies to support the inclusive and sustainable digital growth. Lastly, it ends with the conclusion that the alignment among regional collaboration, AI-based innovation, and spectrum policy is essential to explore the full potential of 5G in ASEAN and mark this region as a future global center for connectivity.